PERANAN KARANG TARUNA DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL MASYARAKAT DI DESA PESANGGRAHAN KECAMATAN BATU – KOTA BATU - Moh. Rowasis; Firman Firdausi (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Youth organization is a village civic organization which is engaged in the field of youth that have mission and vision while has an important role to develop village social society welfare. Youth organization at pesanggrahan village is an organization which is under Pesanggrahan auspices villages and it working in that region itself. Youth organization is an important organization that it does not look in one eyes only, because there are many people interpreted it as an organization that cannot be grown and had no activity and does not have a role.This research used the qualitative research, this type of research instrument is researchers it self, interviewing guidelines, field note. The technique of data collection was done through observation, interviews, documentation. While data analysis is a data analysis interactive model that consists of data collection, data presentation, data reduction, and conclusion. This research may eventually reveal that: (1) the role of youth organizaion in improving the welfare of the villagers either appropriate although in practice is still not optimally. (2) the obstacles of youth organization in improving the welfare of the villagers lack of labor from any member of the Executive Board and in carrying out activities and auth as youth organization. Then set the time to lack in not always collide with an activity that is private. Key Words: Role, youth organization, Welfare, Empowerment Abstrak: Karang taruna merupakan organisasi kemasyarakatan desa yang bergerak dibidang kepemudaan yang mempunyai visi dan misi serta mempunyai peranan penting untuk meningkatkan kesejahteraan sosial masyarakat desa. Karang Taruna merupakan organisasi penting bukan hanya dipandang sebelah mata, karena kebanyakan orang-orang menginterpretasikan sebagai organisasi yang tidak dapat berkembang dan tidak punya kegiatan serta tidak mempunyai peranan.Penelitian ini menggunakan jenis penelitian kualitatif, instrumen penelitian ini adalah peneliti sendiri, pedoman wawancara, catatan lapangan. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi. Sedangkan analisis data yang digunakan adalah analisis data model interaktif yang terdiri dari pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini akhirnya dapat mengungkapkan bahwa: (1) peranan Karang Taruna dalam meningkatkan kesejahteraan masyarakat desa cendrung baik meskipun dalam pelaksanaannya masih belum maksimal. (2) hambatan karang taruna dalam meningkatkan kesejahteraan masyarakat desa kurangnya tenaga kerja dari setiap pengurus dan anggota dalam menjalankan kegiatan dan tupoksi sebagai Karang Taruna. Kemudian kurangnya dalam mengatur waktu untuk tidak selalu berbenturan dengan kegiatan yang sifatnya pribadi. Kata Kunci: Peranan, Karang Taruna, Kesejahteraan, Pemberdayaan